Peace with Guarantees of Life and Territory for Colombian Peasants: A Fight That Doesn't Cost Us Our Lives. "Let Us Defend Our Defenders" - Lledín Vitos, Julia (2017)
This article gathers the main findings of a research project the authors conducted as part of the Permanent Committee for the Defense of Human Rights on the situation of human rights defenders (HRDs) in Colombia's rural contexts. The research included the following components: interviews with organizations and institutions working on the issue of protection; the implementation of a survey of 174 HRDs from twelve departments of the country; and the implementation of seven regional workshops, with the participation of 150 defenders, where participatory methodologies for risk analysis and research were used. From the analysis of the information, it was concluded that the majority had been victims of some type of aggression by reason of their work. The risks human rights defenders face in Colombia are related with the armed conflict, but also with the struggles for land and territory. The bodies responsible for the assaults were, fundamentally, the paramilitary successors and agents of the State, especially the Army. As a result of the research, it was established that the protection in the rural contexts requires differential responses by the State; these should respond to a combination of individual and collective measures of prevention, protection, and self-protection, which have turned out to be effective from the experience of the people.